Factors Influencing the Implementation of SAK EMKM on MSMEs in the Culinary Sector in Ambon City - Karepesina, Mochdar; Loupatty, Linda Grace; Yuniarti Layn, Yuyun (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
This study aims to determine the factors that influence the implementation of SAK EMKM in MSMEs in the culinary sector of Ambon City, the factors studied are Socialization, Educational Background, Business Size, Perception of MSME actors & Accounting Understanding. The data used in this study is primary data obtained through interviews with MSME actors in Ambon City. The informants in this study were MSMEs in the culinary sector located in Ambon City by taking 4 informants representing each range of Micro, Small and Medium. Data analysis techniques used data reduction, data presentation, and drawing conclusions. The results showed that the four informants had never received socialization from the government, but there was a perception factor of MSME actors that made them want to implement SAK EMKM. The educational background of accounting is relevant to financial reports, making informants able to implement SAK EMKM, and vice versa. MSME actors with medium business sizes can not only implement SAK EMKM but small and micro businesses can also. The four informants have the same perception regarding the benefits of financial reports based on SAK EMKM. Understanding accounting improves the quality of financial reports, helps develop business conditions and allows to effectively evaluate their financial performance